Cytology of Bile Duct Brushings: Streaming Ahead with Time - Lahori, Mega; Andotra, Urvashi; Malhotra, Aneeta Singh (Annals of Pathology and Laboratory Medicine, 2022)
Endoscopic retrograde brush cytology of the biliary duct is an established tool for evaluation of obstructive biliary strictures or screening of primary sclerosing cholangitis (PSC) patients for dysplasia. It is a simple, minimally invasive procedure that can be performed during a therapeutic ERCP. Most authors have reported a sensitivity of 30-60% and a specificity of 90-100%. A positive result can be a reliable indicator of malignant neoplasm. However, there is no standardized reporting terminology designed specifically for bile duct brushings. Majority of bile duct brushings yield either benign ductal epithelium, reactive atypia of ductal epithelium or suspicious/positive for malignancy. Diagnosing malignancy in bile duct brushings is based on a constellation of cytologic features, and consideration of the overall picture- clinical presentation, radiology/endoscopy findings, etc. Different studies have highlighted various key features for diagnosing malignancy in bile duct brushings. Features most consistently associated with a malignant category are- loss of honeycomb architecture, 3D clusters, high n:c ratio, anisonucleosis (â‰¥1:4 variation), irregular nuclear outlines, coarse clumped chromatin, and single malignant cells in the background. The utility of biliary brush cytology has been expanded by using FISH, immunocytochemistry, and Next-generation sequencing.